Antioxidant Status of Liver and Kidney Homogenates from Hyperglycemic Rats Administered with Single and Combinatorial Herbal Formulations - Ojiako, Okey Alphonsus; Chikezie, Paul Chidoka; Ogbuji, Agomuo Chizaramoku (Free Radicals and Antioxidants)
Aims: The present study ascertained the comparative capacities of single and combinatorial herbal formulations of Acanthus montanus, Emilia coccinea, Hibiscus rosasinensis and Asystasia gangetica to exert glycemic control and ameliorate oxidative stress in renal and hepatic tissues of alloxan-induced hyperglycemic rats (HyGR) following 30 days treatment. Materials and Methods: Phytochemical composition of the herbal extracts and fasting plasma glucose concentration (FPGC) of the rats were measured by standard methods. The post mitochondrial supernatant fractions (PMSF) of renal and hepatic tissues homogenates were measured for activity levels of glutathione peroxidase (GPOx), superoxide dismutase (SOD) and catalase (CAT) as well as glutathione (GSH) concentration. Results: Comparatively, flavonoids were the most abundant phytochemical present in the four herbal extracts. FPGC of treated HyGR was within the range of 66.30 ± 0.71- 133.00 ± 0.63 mg/dL as against the untreated hyperglycemic rat group=368.20 ± 0.72 mg/dL (p<0.05). At the end of the experimental time, treated HyGR liver SOD activities were lower than that of normal group (p<0.05). Liver and kidney GPOx activities of HyGR were 2.36 folds and 3.93 folds lower than the normal rats. Furthermore, liver and kidney CAT activities of the treated HyGR were significantly (p<0.05) lower than the normal rats, whereas liver and kidney GSH/ GSSG ratios were significantly (p<0.05) increased when compared with treated HyGR. Conclusion: Combinatorial herbal formulations exerted greater glycemic control than the single herbal formulations and caused a sparing effect on renal and hepatic antioxidants against reactive oxygen species.
Keywords: Antioxidant; Hepatic; Hyperglycemia; Phytochemicals; Renal